Cognitive remediation for people with bipolar disorder: The contribution of session attendance and therapy components to cognitive and functional outcomes. (August 2022) - Tsapekos, Dimosthenis; Strawbridge, Rebecca; Wykes, Til; Young, Allan H.; Cella, Matteo
Abstract: Background: Cognitive remediation (CR) can reduce cognitive and functional difficulties in people with bipolar disorder (BD). To date, there is limited evidence on the contribution of session attendance and therapy components to treatment outcomes. This study explores whether attendance and core CR components contribute to treatment outcomes. Methods: This is a secondary analysis using data from a randomized controlled trial comparing CR plus treatment-as-usual (TAU; n = 40) to TAU only (n = 40) in euthymic people with BD. Session attendance was measured by number of sessions and by achieving therapy completion, pre-defined as attending ≥20 sessions. We used instrumental variable analysis to examine the effect of attendance on treatment outcomes. We then considered the association between core therapy components (i.e., massed practice, errorless learning, strategy use, therapist contact) and post-treatment outcome changes using correlation. Results: The CR group improved significantly in measure of global cognition, psychosocial functioning, and goal attainment. Therapy recipients attended 27.1 sessions on average, with 32 (80%) completing the minimum number of 20 sessions. Attending more sessions and achieving therapy completion were associated with improved treatment outcomes, but this relationship was not significant within the subgroup of CR completers. Improvement in psychosocial functioning was associated with therapist contact and goal attainment with selecting useful strategies during therapy. Conclusions: Our findings highlight the relevance of session attendance, specifically the importance of achieving a minimum threshold of CR sessions, for outcome improvement. Strategy use and therapist contact might facilitate improvements in psychosocial functioning and personal recovery goals. Highlights: CR may improve cognition, functioning and goal attainment in patients with BD. 32 participants (80%) in the CR group achieved therapy completion (≥20 sessions). Therapy completion modified the effect of CR across treatment outcomes. 20 sessions might represent a "minimum therapeutic dose" of CR. Strategy use and therapist contact might contribute to functional improvements.